REKONSTRUKSI KEBEBASAN HAKIM DALAM MEMUTUS PERKARA PIDANA BERBASIS HUKUM PROGRESIF - Safni Kholidah Hasibuan; Erdianto '; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
As the evolution continues to grow from the scientific side, the idea to establish the existence of jurisprudence to be, True science is also growing. It should be noted carefully that in taking legal action or law enforcement then, law enforcement does not solely work only to see the law in its foundation as the rule of law only, but also should build on the foundations of other, more important, the bases were formulated by Radbruch law as a fundamental value, namely,certainty,justice,andexpediency. Judicial independence is the guarantee of the implementation of independent judicial power as outlined in the Judicial Authority Act No. 48 of 2009 states that